2012
DOI: 10.1103/physrevb.86.155202
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the significantly enhanced optical transitions in layered boron nitride

Abstract: It is normally expected that an excellent optical material should have p → s-like transitions at the absorption edge. This is because the strength of p → s-like transitions usually is much stronger than those of p → p transitions, especially in those ionic semiconductors where the electronic states are more localized and behave as atomic characters. Here, we demonstrate an exception that the luminescence intensity of hexagonal boron nitride (h-BN) could be at least two orders of magnitude greater than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…Obviously, the well-ordered SiH x layered structures we discovered here could overcome the large lattice-mismatch issue in InGaN alloys for high-efficiency white lighting. Moreover, it is found that layered materials have unique advantages over the conventional bulk materials for lighting because of the very strong optical transition rates at their band edges [59,62]. As far as we know, this is the first report on the discovery of silicon-based materials for white lighting, which can extend our current knowledge of the use of silicon for optoelectronics.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Obviously, the well-ordered SiH x layered structures we discovered here could overcome the large lattice-mismatch issue in InGaN alloys for high-efficiency white lighting. Moreover, it is found that layered materials have unique advantages over the conventional bulk materials for lighting because of the very strong optical transition rates at their band edges [59,62]. As far as we know, this is the first report on the discovery of silicon-based materials for white lighting, which can extend our current knowledge of the use of silicon for optoelectronics.…”
mentioning
confidence: 63%
“…where ε 2 is the calculated imaginary part of the dielectric function [62,70], c is the speed of light, and Δz is the size of the supercell in the layer-normal direction. Equation (5) (α ¼ ε 2 ω=cn) for a monolayer material with small thickness Δz.…”
mentioning
confidence: 99%
“…The transition region between Urbach tail states and the indirect band edge could include states from dangling bonds, similar to those found in micro-and poly-crystalline Si films. However, despite the debating issue concerning the bandgap, clearly, the band-edge emission efficiency in hBN is unusually high due to its layered structure [25]. The layer structured hBN provides a natural 2D system which result in a sharp "step"-like density of states and increase in the exciton binding energy and oscillator strength.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as schematically shown in Figs. 1(b) and 1(c), this layer-structured alloy system potentially possesses an extremely large energy gap (E g ) variation from around 6.4 eV for h-BN [1][2][3] to 0 for graphite, following roughly the relation of…”
Section: Introductionmentioning
confidence: 99%
“…In the plot, we also neglected the exciton binding energy, which is about 740 meV in h-BN. [1][2][3] resistive semiconductors (undoped h-BN) to semi-metal (graphite). The h-(BN) 1-x (C 2 ) x material system would complement III-nitride wide bandgap semiconductors and carbon based nanostructured materials and appears to be highly promising for technologically significant photonic and electronic device applications.…”
Section: Introductionmentioning
confidence: 99%